Global cancer surgery: delivering safe, affordable, and timely cancer surgery. Issue 11 (September 2015) - Sullivan, Richard; Alatise, Olusegun Isaac; Anderson, Benjamin O; Audisio, Riccardo; Autier, Philippe; Aggarwal, Ajay; Balch, Charles; Brennan, Murray F; Dare, Anna; D'Cruz, Anil; Eggermont, Alexander M M; Fleming, Kenneth; et al.
Summary Surgery is essential for global cancer care in all resource settings. Of the 15·2 million new cases of cancer in 2015, over 80% of cases will need surgery, some several times. By 2030, we estimate that annually 45 million surgical procedures will be needed worldwide. Yet, less than 25% of patients with cancer worldwide actually get safe, affordable, or timely surgery. This Commission on global cancer surgery, building on Global Surgery 2030, has examined the state of global cancer surgery through an analysis of the burden of surgical disease and breadth of cancer surgery, economics and financing, factors for strengthening surgical systems for cancer with multiple-country studies, the research agenda, and the political factors that frame policy making in this area. We found wide equity and economic gaps in global cancer surgery. Many patients throughout the world do not have access to cancer surgery, and the failure to train more cancer surgeons and strengthen systems could result in as much as US$6·2 trillion in lost cumulative gross domestic product by 2030. Many of the key adjunct treatment modalities for cancer surgery—eg, pathology and imaging—are also inadequate. Our analysis identified substantial issues, but also highlights solutions and innovations. Issues of access, a paucity of investment in public surgical systems, low investment in research, and training and education gaps are remarkably widespread. Solutions include better regulated public systems, international partnerships, super-centralisation of surgical services, novel surgical clinical trials, and new approaches to improve quality and scale up cancer surgical systems through education and training. Our key messages are directed at many global stakeholders, but the central message is that to deliver safe, affordable, and timely cancer surgery to all, surgery must be at the heart of global and national cancer control planning.